2000
DOI: 10.1073/pnas.97.20.10814
|View full text |Cite
|
Sign up to set email alerts
|

Tid1/Rdh54 promotes colocalization of Rad51 and Dmc1 during meiotic recombination

Abstract: Two RecA homologs, Rad51 and Dmc1, assemble as cytologically visible complexes (foci) at the same sites on meiotic chromosomes. Time course analysis confirms that co-foci appear and disappear as the single predominant form. A large fraction of co-foci are eliminated in a red1 mutant, which is expected as a characteristic of the interhomolog-specific recombination pathway. Previous studies suggested that normal Dmc1 loading depends on Rad51. We show here that a mutation in TID1͞RDH54, encoding a RAD54 homolog, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
230
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(249 citation statements)
references
References 45 publications
19
230
0
Order By: Relevance
“…It was previously suggested that Rad51 might load on one end formed by a DSB while Dmc1 loads on the other (Shinohara et al 2000). This hypothetical configuration works well with the present proposal, although other configurations allowing for support of Dmc1 by Rad51 can be imagined as well.…”
Section: A Model For the Contribution Of Dmc1 And Rad51 To Interhomolsupporting
confidence: 73%
“…It was previously suggested that Rad51 might load on one end formed by a DSB while Dmc1 loads on the other (Shinohara et al 2000). This hypothetical configuration works well with the present proposal, although other configurations allowing for support of Dmc1 by Rad51 can be imagined as well.…”
Section: A Model For the Contribution Of Dmc1 And Rad51 To Interhomolsupporting
confidence: 73%
“…Consistent with this are immunological observations that reveal a side-by-side distribution of the two recombinases (Tarsounas et al 1999;Shinohara et al 2000). In addition, biochemical studies indicate that the two ends of the resected DSB behave differently, with one, proposed to be Dmc1-coated, responsible for the initial strand invasion of the homolog, while the second is captured at a later stage in the recombination pathway (Hunter and Kleckner 2001).…”
Section: Chromatin Loading Of Atdmc1 and Atrad51 Is Asynchronoussupporting
confidence: 72%
“…Studies in budding yeast have led to the proposal that there may be inherent asymmetry in the way that Dmc1 and Rad51 interact with the two ends of the meiotic DSBs (Shinohara et al 2000;Hunter and Kleckner 2001). Consistent with this are immunological observations that reveal a side-by-side distribution of the two recombinases (Tarsounas et al 1999;Shinohara et al 2000).…”
Section: Chromatin Loading Of Atdmc1 and Atrad51 Is Asynchronousmentioning
confidence: 99%
“…Much of our current understanding of the mechanism of meiotic recombination comes from studies carried out in yeast, partly because rad51 mutants are viable in this organism. In S. cerevisiae, the appearance of Dmc1/Rad51 foci coincides with the formation of Spo11-induced DSBs, and the foci tend to disappear as the chromosomes synapse (Shinohara et al, 2000).…”
Section: Predominant In G1mentioning
confidence: 99%